2023
DOI: 10.1021/cbmi.3c00011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Dual-Targeted ECO/siRNA Nanoparticles against an Oncogenic lncRNA for Triple Negative Breast Cancer Therapy with Magnetic Resonance Molecular Imaging

Abstract: Differentiation antagonizing noncoding RNA (DANCR) is recognized as an oncogenic long noncoding RNA (lncRNA) overexpressed in triple negative breast cancer (TNBC). We showed in a previous study that RNAi with targeted multifunctional ionizable lipid ECO/siRNA nanoparticles was effective to regulate this undruggable target for effective treatment of TNBC. In this study, we developed dual-targeted ECO/siDANCR nanoparticles by targeting a tumor extracellular matrix oncoprotein, extradomain B fibronectin (EDB-FN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The results imply that the chemotherapy induced the transition of the cancer cells to a resistant phenotype. ZD2-siDANCR-ELNP were effective to down-regulate the expression of both DANCR and EDB-FN in naïve cancer cells and paclitaxel-treated cells, which was consistent with the previous observation using ZD2/RGD-PEG-ECO/siDANCR . ZD2-siDANCR-ELNP transfection sensitized the TNBC cells to paclitaxel and reduced the dose necessary to achieve the same reduction in cell viability as ZD2-siNS-ELNP transfection or no transfection in MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results imply that the chemotherapy induced the transition of the cancer cells to a resistant phenotype. ZD2-siDANCR-ELNP were effective to down-regulate the expression of both DANCR and EDB-FN in naïve cancer cells and paclitaxel-treated cells, which was consistent with the previous observation using ZD2/RGD-PEG-ECO/siDANCR . ZD2-siDANCR-ELNP transfection sensitized the TNBC cells to paclitaxel and reduced the dose necessary to achieve the same reduction in cell viability as ZD2-siNS-ELNP transfection or no transfection in MDA-MB-231 cells.…”
Section: Discussionsupporting
confidence: 90%
“…MRMI is a high-resolution molecular imaging modality that can provide detailed molecular information about solid tumors during cancer therapies. MT218-MRMI noninvasively visualizes the expression of EDB-FN for the detection, characterization, and therapeutic response of multiple cancers, including TNBC. ,, In this study, MT218-MRMI revealed the dynamic and heterogeneous changes in EDB-FN expression in tumor ECM in correlation with therapeutic outcomes in response to various treatments. Although the three therapies showed similar inhibition of TNBC growth after treatments for 6 weeks, MT218-MRMI clearly differentiated tumor responses based on the molecular signature of EDB-FN, which was supported by histopathological and/or immunohistochemical analyses.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) has been widely used in clinical diagnostics . MRI is a noninvasive technique with the advantages of having extremely high spatial resolution and the absence of radiation exposure. This feature allows early detection of even tumors as small as a few hundred cells and hundreds of micrometers in size . However, MRI has low sensitivity and usually requires a contrast agent to increase its sensitivity.…”
Section: Construction Of Targeting Peptide-based Imaging Reagentsmentioning
confidence: 99%
“…157−160 This feature allows early detection even tumors as small as a few hundred cells and hundreds of micrometers in size. 161 However, MRI has low sensitivity and usually requires a contrast agent to increase its sensitivity. Generally, MRI contrast agents are broadly classified into longitudinal relaxation contrast agents (T1 preparation) and transverse relaxation contrast agents (T2 preparation).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%